1993
DOI: 10.1029/93eo00271
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami field survey of the 1992 Nicaragua earthquake

Abstract: An earthquake with surface magnitude (Ms ) 7.0 occurred 100 km off the Nicaraguan coast on September 2, 1992 (GMT). Despite its moderate size, this earthquake generated a sizable tsunami, which caused extensive damage along the coast of Nicaragua. In late September, about 170 people, mostly children, were listed dead or missing; 500 were listed injured; and over 13,000 were listed homeless, with more than 1500 homes destroyed. Damage was the most significant since the 1983 Japan Sea earthquake tsunami, which k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 5 publications
2
41
0
1
Order By: Relevance
“…The characteristics of this kind of earthquakes are the slow rupture velocity, the long duration, the shallow dipping thrust fault and the shallow focus (Pelayo and Wiens, 1992;Okal and Newman, 2001;López and Okal, 2006;Okal and Borrero, 2011). The analysis of the Nicaragua 1992 earthquake confirmed this earthquake as a slow tsunami earthquake Imamura et al, 1993;Satake, 1994;Velasco et al, 1994) in a subduction interface with low rigidity (Satake et al, 1993;Piatanesi et al, 1996).…”
Section: Local Sourcesmentioning
confidence: 85%
“…The characteristics of this kind of earthquakes are the slow rupture velocity, the long duration, the shallow dipping thrust fault and the shallow focus (Pelayo and Wiens, 1992;Okal and Newman, 2001;López and Okal, 2006;Okal and Borrero, 2011). The analysis of the Nicaragua 1992 earthquake confirmed this earthquake as a slow tsunami earthquake Imamura et al, 1993;Satake, 1994;Velasco et al, 1994) in a subduction interface with low rigidity (Satake et al, 1993;Piatanesi et al, 1996).…”
Section: Local Sourcesmentioning
confidence: 85%
“…Field survey of tsunami run-up heights Satake et al 1993) showed that the maximum tsunami run-up height was 9.9 m above mean sea level, although the maximum intensity in Modified Mercalli scale was only III. This weak intensity with a large tsunami indicates that this was an unusual 'tsunami earthquake' (Satake 1994).…”
Section: Tsunami Numerical Simulationmentioning
confidence: 99%
“…The 1992 Nicaragua earthquake occurred off the Pacific coast of Central America and generated a much larger tsunami than expected from its surface wave magnitude of M s 7.2; so the earthquake is classified as a 'tsunami earthquake' (Satake et al 1993). Seismological analysis of the earthquake (Ide et al 1993, Kanamori andKikuchi 1993) and tsunami waveform analysis (Satake 1994) showed that the seismic moment M 0 is 3-4 9 10 20 Nm (Mw = 7.6-7.7).…”
Section: Introductionmentioning
confidence: 99%
“…It was a tsunami earthquake that ruptured probably the shallowest section of the subduction interface (Satake, 1994;Velasco et al, 1994). Its effects were very destructive in Nicaragua, where wave heights reached more than 9 m, but the tsunami was recorded along the Salvadorian and Costa Rican pacific coast of Central America too (Baptista et al, 1993;Femandez and Alvarado-Delgado, 2005;Femandez et al, 2004;Satake et al, 1993).…”
Section: Discussionmentioning
confidence: 99%